THERAPEUTIC AND SPORT TRAINING OF SITTING VOLLEYBALL PLAYERS AS ONE OF THE SPECIFIC AREAS OF EDUCATION - Ida Kabok (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The motivation is one of the most important competents of the docility, it is the "propelling power" of our activities. People could be stimulated to do sportinfl uence on the personality is known- by a many different things. Sport means both happiness and the key of the independence for the people with physical impairment. With the help of our research's results we would like to introduce what motivates physically impaired people to do regular sport.